Indirect expressions of the warrior gene responsible for the enzyme catechol-o-methyltransferase (COMT) in situations of academic stress (Research, Society and Development, 2024)
The term "warrior gene" is commonly used to describe genetic variations that may impact human behavior, such as aggression, impulsivity, and stress tolerance. However, there is increasing evidence that important genetic variants can alter the activity within specific neuronal circuits and, therefore, influence specific cognitive-affective phenomena. A single nucleotide polymorphism in the catechol-O-methyltransferase (COMT) gene leads to a genetic variant that regulates the metabolism of catecholamines, mainly dopamine. Therefore, genetic variations in the COMT gene may influence the activity of this enzyme, resulting in individual disparities in dopamine regulation and, consequently, shaping personality traits and behavioral patterns. Objective to understand and indirectly relate the different expressions of the COMT gene in academics subjected to adverse stress situations. For this study, a practical social experiment was conducted in two stages of questionnaires. The first stage was conducted in a comfortable situation, and the second stage involved stress induction. The results indicate that academics aged 17 to 23 with possible Val158Val genotypes exhibit a faster degradation of dopamine, resulting in lower stress levels, while those with the possible Met158Met genotype have an accumulation of dopamine, leading to a more intense stress response, especially in adverse situations. In the end, relationships were established that differentiate the COMT alleles in homozygotes (Val158Val; Met158Met) and heterozygotes (Val158Met) to highlight differences in dopamine degradation in the prefrontal cortex.